Neurological intact survival with rescue mechanical circulatory support for refractory out-of-hospital cardiac arrest despite long low-flow times. (2nd May 2022) - Moerk, S; Christensen, S; Boetker, MT; Tang, M; Terkelsen, CJ
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The potential window for using mechanical circulatory support (MCS) for refractory out-of-hospital cardiac arrest (OHCA) remain unsettled. It has been proposed that a cut-off limit defined as the golden hour may produce higher survival with good neurological outcome. Purpose: The present study analyzed the association of low-flow time and neurological intact survival (Cerebral Performance Categories 1-2) at discharge between patients receiving conventional cardiopulmonary resuscitation (CCPR) and MCS. Methods: The present retrospective, observational, single centre study from 2015-2019 included all consecutive OHCA patients, who were treated with MCS for refractory OHCA or received CCPR. Low-flow time was defined as the time from CPR to deployment of either veno-arterial extracorporeal membrane oxygenation or Impella support for the MCS group. Time from CPR to return of spontaneous circulation or termination of treatment was recorded for the CCPR group. Rate of neurological intact survival at discharge were analyzed for both groups. Results: A total of 101 patients were treated with MCS and 914 patients received CCPR. The MCS group was significantly younger with a median age of 56 (IQR, 46-62) years compared to 67 (IQR, 57-74) years, p < 0.001. In the CCPR group, short low-flow times (0-20 minutes) were associated with high survival with good neurological outcome at discharge. There were no survivors with low-flow times exceeding 70 minutes. All patients receiving MCS survived at low-flow times 31-60 minutes, however neurological intact survival dropped to 21% at low-flow times > 80 minutes. Conclusion: Patients treated with MCS with low-flow time 70-80 minutes did show similar favorable neurological outcome at discharge as patients receiving CCPR with low-flow < 10 minutes. Despite, low-flow times exceeding 80 minutes, patients treated with MCS still presented high survival rate of 21%. Hence, the data in this study does not support a golden hour for MCS.